A method for utilizing lead-zinc mine slag as a resource for mine road paving
By stabilizing and curing the lead-zinc slag, solidified paving materials that can be used for mining road paving are formed, which solves the problem of soil erosion caused by loose heavy metals and structures in the slag, and realizes the resource utilization of slag and the environmentally friendly treatment of waste.
Patent Information
- Application Number
- CN202310325926.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-03-30
AI Technical Summary
Lead-zinc ore slag contains high content of heavy metals and has a loose structure, which can easily lead to soil erosion. The existing technology lacks effective treatment and utilization methods.
By stabilizing and curing the lead-zinc slag, a solidified paving material can be used for mining road paving. Specific steps include: pretreatment (stability and curing treatment), laying a slag curing layer, anti-seepage layer, base layer, anti-seepage concrete surface layer, side barrier wall and gap joint filling expansion, etc.
It effectively reduces the precipitation of harmful substances in the slag, enhances the strength of the slag, prevents rainwater from infiltration, extends the service life of the road, and realizes the resource utilization of slag and environmentally friendly waste treatment.
Smart Images

Figure CN116356628B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of slag waste disposal, and in particular to a method for utilizing lead-zinc mine slag as a resource for mine road paving. Background Art
[0002] Lead-zinc ore refers to minerals rich in the metal elements lead and zinc. Lead-zinc mines in my country are mainly concentrated in Yunnan, Gansu, Guangdong, Hunan, Fujian and Guangxi. Lead-zinc ore slag refers to the stripping material used in the process of lead-zinc mining. For lead-zinc ore slag, the common treatment method is to pave the mine road with the slag in the open air. Due to the high content of heavy metals such as lead, zinc and cadmium in the slag and the loose original structure of the slag, it is very easy to cause soil erosion.
[0003] In order to solve the above problems, the present invention provides a road paving method for utilizing lead-zinc mine slag waste resources for paving mine roads. Summary of the invention
[0004] Therefore, in order to solve the above-mentioned problems, the present invention proposes a method for utilizing lead-zinc mine slag waste resources in mine road paving.
[0005] In order to solve the above technical problems, the solution adopted by the present invention is: a method for utilizing lead-zinc ore slag as a resource for paving mine roads, comprising the following paving method steps:
[0006] A1: Pre-treat the lead-zinc slag. The pre-treatment steps are as follows:
[0007] B1: Stabilize the lead-zinc slag: Add lead-zinc slag, stabilizer and water into a mixer and mix them evenly. The addition ratio of stabilizer is 0.5%-2% of the weight of slag. After mixing evenly, the moisture content of slag is 18%-22%;
[0008] B2: After stabilization, the lead-zinc slag is solidified: stabilized lead-zinc slag, curing agent and water are added into the mixer and stirred evenly to form a lead-zinc slag paving material that can be automatically solidified. The amount of curing agent added is 4%-7% of the weight of the slag, and the amount of water added is 2%-3.5% of the weight of the slag. The strength of the solidified body after curing reaches more than 1.5Mpa;
[0009] A2: Laying the slag solidification layer:
[0010] A paving road is excavated on the surface of the paving road, baffles are fixed on both sides of the paving road to prevent the material from scattering and spreading to both sides, the lead-zinc slag paving material is evenly laid on the paving road between the baffles on both sides and compacted, and maintained until the lead-zinc slag paving material is solidified to form a slag solidification layer;
[0011] A3: After the solidification is qualified, lay the anti-seepage layer on the slag solidification layer:
[0012] The anti-seepage layer includes two layers of filament non-woven fabrics and a layer of HDPE geomembrane. A layer of filament non-woven fabric is first laid on the surface of the slag solidification layer, then a layer of HDPE geomembrane is laid, and finally a layer of filament non-woven fabric is laid. The thickness of the filament non-woven fabric is 3-7mm and the weight is 800g / m 2 , the thickness of the HDPE geomembrane is 1-3mm;
[0013] A4: Lay a base layer on the anti-seepage layer to stabilize the anti-seepage layer and the slag solidification layer:
[0014] The material of the base layer is 5% cement-stabilized crushed stone, and its seven-day unconfined compressive strength is not less than 3Mpa. The thickness of the base layer is 25-35mm, and the base layer is cured until it is completely solidified;
[0015] A5: Lay the impermeable concrete surface layer on the base:
[0016] The surface layer is made of impermeable concrete with a laying thickness of 15-25 mm, a flexural strength of not less than 4.5 Mpa, and an impermeability grade of P6. The impermeable concrete surface layer is cured until it is completely solidified;
[0017] A6: Build a side barrier wall outside the baffle to prevent rainwater from penetrating into the slag solidification layer from the side:
[0018] Remove the baffles on both sides of the road, continue to dig the bottom of the unpaved road downward to form a side barrier groove, fill and pave C30 plain concrete in the side barrier groove, and after solidification, form a side barrier wall whose lowest position is lower than the slag solidification layer to prevent water and soil from penetrating into the slag solidification layer from the side and soaking out heavy metals. The anti-seepage grade of the side barrier wall is P6, and the highest point of the side barrier wall is flush with the anti-seepage concrete surface layer. Maintain the side barrier wall until it is completely solidified;
[0019] A7: The gaps between the side barrier wall and the surface layer, as well as the gaps caused by the segmented paving of the surface layer, are caulked and expanded to waterproof and seal:
[0020] Asphalt and expansion agent are evenly mixed to form a caulking agent, which is then filled into the gaps. The asphalt fills the gaps under the action of the expansion agent, and the caulking agent is cured until it is completely solidified.
[0021] A further improvement is that: the step A6 further includes the following steps:
[0022] A6: Build a side barrier wall outside the baffle to prevent rainwater from penetrating into the slag solidification layer from the side:
[0023] The baffles on both sides of the road are removed, and the bottom of the unpaved road is further deepened to form a side barrier groove. A drainage ditch template is built in the inner barrier groove on the inner side of the road, and a diversion wall template for diverting rainwater to the outside is built in the outer barrier groove on the outer side of the road. C30 plain concrete is filled and paved in the drainage ditch template and the diversion wall template. The inner and outer barrier walls are cured until they are completely solidified. After solidification, an inner barrier wall with a drainage ditch on the top and an outer barrier wall with a diversion wall on the top are formed respectively. The lowest positions of the outer barrier wall and the inner barrier wall are both lower than the slag solidification layer to prevent water and soil from penetrating into the slag solidification layer from the side and leaching out heavy metals.
[0024] A further improvement is that the stabilizer is a zeolite molecular sieve adsorbent.
[0025] A further improvement is that the curing agent is a silicate curing agent.
[0026] A further improvement is that the expansion agent is a mixture of silicon oxide, a polycarboxylic acid type collapse retaining agent, a shrinkage-reducing polycarboxylic acid water-reducing agent, a styrene copolymer carboxyl compound, and a lignin sulfonate.
[0027] By adopting the above technical solution, the beneficial effects of the present invention are:
[0028] After the ore is stripped of the usable materials, it becomes slag waste. The annual ore mining volume is large, and a lot of ore waste is generated. At present, there is no complete treatment system for slag. Most of them are directly discarded or laid directly on the road or directly buried in pits. Most of the slag is loose, and the scope of the slag will expand under the influence of rain and wind, which is very likely to cause soil erosion. In this case, the anti-seepage concrete surface layer, base layer, anti-seepage layer, and side barrier wall are used for layer-by-layer protection to maximize the prevention of contact between rainwater and slag. The slag is stabilized and solidified before laying, which reduces the precipitation of harmful substances in the slag. At the same time, the strength of the slag can be effectively increased after solidification. The paved road will not have dents and cracks when heavy vehicles pass by, effectively preventing the infiltration of rainwater. The gaps generated during the paving process are also filled with asphalt expansion, which prevents rainwater from infiltrating from top to bottom. At the same time, the depth of the side barrier wall is greater than the laying depth of the slag solidification layer, which prevents rainwater from infiltrating horizontally. The diversion wall and the drainage ditch can help rainwater stay away from the slag solidification layer. The slag solidification layer is prevented from contacting with rainwater in many directions. At the same time, the slag is treated to reduce the precipitation of harmful substances in the slag, forming a complete ore treatment system, which can effectively use slag to participate in road paving, rationalize the treatment of slag, and realize waste utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The invention discloses a construction flow chart of a method for utilizing lead-zinc ore slag as a resource for paving mine roads.
[0030] Figure 2 It is a top view of a road paved by a method of utilizing lead-zinc ore slag as a resource for paving mine roads according to an embodiment of the present invention.
[0031] Figure 3 yes Figure 2 Schematic diagram of the internal structure along line AA.
[0032] Figure 4 yes Figure 3 A magnified view of the local structure at point B in the middle.
[0033] Figure 5 This is a comparison chart of lead content data in the J1 area before and after remediation in a method for utilizing lead-zinc mine slag resources for mine road paving in an embodiment of the present invention.
[0034] Figure 6 This is a comparison chart of lead content data in the F1 area before and after remediation in a method for utilizing lead-zinc mine slag resources for mine road paving in an embodiment of the present invention.
[0035] Figure 7 This is a comparison chart of lead content data in the F3 area before and after remediation in a method for utilizing lead-zinc mine slag as a resource for mine road paving in an embodiment of the present invention.
[0036] Figure 8 This is a comparison chart of lead content data in the F4 area before and after remediation in a method for utilizing lead-zinc mine slag as a resource for mine road paving in an embodiment of the present invention.
[0037] Fig. 9 This is a comparison chart of suspended matter content data in the J1 area before and after remediation in a method for utilizing lead-zinc mine slag resources for mine road paving in an embodiment of the present invention.
[0038] Fig.10 This is a comparison chart of suspended matter content data in the X1 area before and after remediation in a method for utilizing lead-zinc mine slag resources for mine road paving in an embodiment of the present invention.
[0039] Fig.11 It is a comparison chart of suspended matter content data in F1 area before and after remediation in a method for utilizing lead-zinc mine slag resources for mine road paving in an embodiment of the present invention.
[0040] Fig.12 This is a comparison chart of suspended matter content data in the F3 area before and after remediation in a method for utilizing lead-zinc mine slag resources for mine road paving in an embodiment of the present invention.
[0041] Fig.13 This is a comparison chart of suspended matter content data in the F4 area before and after remediation in a method for utilizing lead-zinc mine slag resources for mine road paving in an embodiment of the present invention. DETAILED DESCRIPTION
[0042] The present invention will now be further described with reference to the accompanying drawings and specific embodiments.
[0043] refer to Figures 1 to 13 The embodiment of the present invention discloses a method for utilizing lead-zinc ore slag as a resource for paving mine roads, comprising the following paving method steps:
[0044] A1: Pre-treat the lead-zinc slag. The pre-treatment steps are as follows:
[0045] B1: Stabilize the lead-zinc slag: add lead-zinc slag, stabilizer and water into a mixer and mix them evenly. The stabilizer is added in an amount of 0.5%-2% of the weight of the slag, preferably 1.5%; after mixing evenly, the water content of the slag is 18%-22%, preferably 20%; after stabilization, the concentration of heavy metals precipitated from the slag is lower than the Class III standard limit of the Surface Water Environmental Quality Standard (GB 3838-2002). The stabilizer is a zeolite molecular sieve adsorbent.
[0046] B2: After stabilization, the lead-zinc slag is solidified: stabilized lead-zinc slag, curing agent and water are added to the mixer and stirred evenly to form a lead-zinc slag paving material that can be automatically solidified. The amount of curing agent added is 4%-7% of the weight of the slag, preferably 5%; the amount of water added is 2%-3.5% of the weight of the slag, preferably 3%; the strength of the solidified body after curing reaches more than 1.5Mpa, thereby meeting the "City Road Engineering Construction and Quality Acceptance Specifications". The curing agent is a silicate curing agent.
[0047] A2: Laying slag solidification layer 10:
[0048] A paving road is excavated on the surface of the paved road, baffles are fixed on both sides of the paving road to prevent the material from scattering and spreading to both sides, the lead-zinc slag paving material is evenly laid on the paving road between the baffles on both sides and compacted, and the lead-zinc slag paving material is regularly watered and cured by covering the moisturizing surface layer 13 until the lead-zinc slag paving material is solidified to form a slag solidification layer 10;
[0049] A3: After the solidification is qualified, the anti-seepage layer 11 is laid on the slag solidification layer 10:
[0050] The anti-seepage layer 11 includes two layers of filament non-woven fabric 111 and a layer of HDPE geomembrane 112. A layer of filament non-woven fabric 111 is first laid on the surface of the slag solidification layer 10, and then a layer of HDPE geomembrane 112 is laid, and finally a layer of filament non-woven fabric 111 is laid. The thickness of the filament non-woven fabric 111 is 3-7 mm and the weight is 800 g / m 2The thickness of the filament nonwoven fabric 111 is preferably 5.5 mm. The thickness of the HDPE geomembrane 112 is 1-3 mm, preferably 2 mm.
[0051] A4: Laying a base layer 12 on the impermeable layer 11 for stabilizing the impermeable layer 11 and the slag solidified layer 10:
[0052] The material of the base layer 12 is 5% cement-stabilized crushed stone, and its seven-day unconfined compressive strength is not less than 3Mpa. The thickness of the base layer 12 is 25-35mm, preferably 30mm. The base layer 12 is covered with a moisturizing surface layer 13 and regularly watered and cured until it is completely cured.
[0053] A5: Laying an impermeable concrete surface layer 13 on the base layer 12:
[0054] The material of the surface layer 13 is impermeable concrete, the laying thickness is 15-25mm, the flexural strength is not less than 4.5Mpa, the impermeability grade is P6, and the laying thickness is preferably 20mm. The impermeable concrete surface layer 13 is completely cured by covering the moisturizing surface layer 13 and regularly sprinkling water for maintenance;
[0055] A6: A side barrier wall is built outside the baffle to prevent rainwater from penetrating into the slag solidification layer 10 from the side:
[0056] The baffles on both sides of the road are removed, and the bottom of the unpaved road is further deepened to form a side barrier groove. A drainage ditch 141 template is built in the inner barrier groove on the inner side of the road, and a diversion wall 151 template for diverting rainwater to the outside is built in the outer barrier groove on the outer side of the road. C30 plain concrete is filled and laid in the drainage ditch template and the diversion wall template, and the inner and outer barrier walls 15 are cured until they are completely solidified. After solidification, an inner barrier wall 14 with a drainage ditch 141 on the top and an outer barrier wall 15 with a diversion wall 151 on the top are formed respectively. The lowest positions of the outer barrier wall 15 and the inner barrier wall 14 are both lower than the slag solidification layer 10 to prevent water and soil from penetrating into the slag solidification layer 10 from the side and leaching out heavy metals.
[0057] A7: The gap 16 between the side barrier wall and the surface layer 13, as well as the gap 16 caused by the segmented laying of the surface layer 13, is caulked and expanded to achieve waterproof sealing:
[0058] The asphalt and the expansion agent are evenly mixed to form a caulking agent, which is filled into the gap 16. The asphalt fills the gap 16 under the action of the expansion agent, and water is sprinkled regularly for curing until the caulking agent is completely cured. The expansion agent is a mixture of silicon oxide, polycarboxylic acid type collapse retaining agent, shrinkage-reducing polycarboxylic acid water reducer, styrene co-polycarboxyl compound, and lignin sulfonate.
[0059] The relevant test data are as follows:
[0060] Test samples of the slag solidified layer after stabilization and solidification pretreatment in five areas were taken for testing, and the samples in the five areas were named as: J1, X1, F1, F3, and F4.
[0061] 1. Perform strength test and heavy metal leaching concentration test on regional samples. The test results are as follows:
[0062] (1) The results of the strength test are summarized in the following table:
[0063]
[0064] (2) The statistics of heavy metal leaching concentration monitoring data in J1 area are as follows:
[0065]
[0066] (3) The statistics of heavy metal leaching concentration monitoring data in area X1 are as follows:
[0067]
[0068] (4) The statistics of heavy metal leaching concentration monitoring data in F1 area are as follows:
[0069]
[0070] (5) The statistics of heavy metal leaching concentration monitoring data in F3 area are as follows:
[0071]
[0072] (6) The statistics of heavy metal leaching concentration monitoring data in F4 area are as follows:
[0073]
[0074] 2. The surface water runoff pollution monitoring data before and after the remediation of the five areas J1, X1, F1, F3 and F4 were compared with the lead content and suspended matter before and after the remediation.
[0075] The basic principles, main features and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention shall be defined by the attached claims and their equivalents.
Claims
1. A method for utilizing lead-zinc ore slag as a resource for mine road paving, characterized in that: The paving method includes the following steps: A1: Pre-treat the lead-zinc slag. The pre-treatment steps are as follows: B1: Stabilize the lead-zinc slag: Add lead-zinc slag, stabilizer and water into a mixer and mix them evenly. The addition ratio of stabilizer is 0.5%-2% of the weight of slag. After mixing evenly, the moisture content of slag is 18%-22%; B2: After stabilization, the lead-zinc slag is solidified: stabilized lead-zinc slag, curing agent and water are added into the mixer and stirred evenly to form a lead-zinc slag paving material that can be automatically solidified. The amount of curing agent added is 4%-7% of the weight of the slag, and the amount of water added is 2%-3.5% of the weight of the slag. The strength of the solidified body after curing reaches more than 1.5Mpa; A2: Laying the slag solidification layer: A paving road is excavated on the surface of the paving road, baffles are fixed on both sides of the paving road to prevent the material from scattering and spreading to both sides, the lead-zinc slag paving material is evenly laid on the paving road between the baffles on both sides and compacted, and maintained until the lead-zinc slag paving material is solidified to form a slag solidification layer; A3: After the solidification is qualified, lay the anti-seepage layer on the slag solidification layer: The anti-seepage layer includes two layers of filament non-woven fabrics and a layer of HDPE geomembrane. A layer of filament non-woven fabric is first laid on the surface of the slag solidification layer, and then a layer of HDPE geomembrane is laid, and finally a layer of filament non-woven fabric is laid. The thickness of the filament non-woven fabric is 3-7mm and the weight is 800g / m2. The thickness of the HDPE geomembrane is 1-3mm. A4: Lay a base layer on the anti-seepage layer to stabilize the anti-seepage layer and the slag solidification layer: The material of the base layer is 5% cement-stabilized crushed stone, and its seven-day unconfined compressive strength is not less than 3Mpa. The thickness of the base layer is 25-35mm, and the base layer is cured until it is completely solidified; A5: Lay the impermeable concrete surface layer on the base: The surface layer is made of impermeable concrete with a laying thickness of 15-25 mm, a flexural strength of not less than 4.5 Mpa, and an impermeability grade of P6. The impermeable concrete surface layer is cured until it is completely solidified; A6: Build a side barrier wall outside the baffle to prevent rainwater from penetrating into the slag solidification layer from the side: Remove the baffles on both sides of the road, continue to dig the bottom of the unpaved road downward to form a side barrier groove, fill and pave C30 plain concrete in the side barrier groove, and after solidification, form a side barrier wall whose lowest position is lower than the slag solidification layer to prevent water and soil from penetrating into the slag solidification layer from the side and soaking out heavy metals. The anti-seepage grade of the side barrier wall is P6, and the highest point of the side barrier wall is flush with the anti-seepage concrete surface layer. Maintain the side barrier wall until it is completely solidified; A7: The gaps between the side barrier wall and the surface layer, as well as the gaps caused by the segmented paving of the surface layer, are caulked and expanded to waterproof and seal: Asphalt and expansion agent are evenly mixed to form a caulking agent, which is then filled into the gaps. The asphalt fills the gaps under the action of the expansion agent, and the caulking agent is cured until it is completely solidified.
2. The method for utilizing lead-zinc ore slag as a resource for mine road paving according to claim 1, characterized in that: The step A6 specifically also includes the following steps: A6: Build a side barrier wall outside the baffle to prevent rainwater from penetrating into the slag solidification layer from the side: The baffles on both sides of the road are removed, and the bottom of the unpaved road is further deepened to form a side barrier groove. A drainage ditch template is built in the inner barrier groove on the inner side of the road, and a diversion wall template for diverting rainwater to the outside is built in the outer barrier groove on the outer side of the road. C30 plain concrete is filled and paved in the drainage ditch template and the diversion wall template. The inner and outer barrier walls are cured until they are completely solidified. After solidification, an inner barrier wall with a drainage ditch on the top and an outer barrier wall with a diversion wall on the top are formed respectively. The lowest positions of the outer barrier wall and the inner barrier wall are both lower than the slag solidification layer to prevent water and soil from penetrating into the slag solidification layer from the side and leaching out heavy metals.
3. The method for utilizing lead-zinc ore slag as a resource for mine road paving according to claim 1, characterized in that: The stabilizer is a zeolite molecular sieve adsorbent.
4. The method for utilizing lead-zinc ore slag as a resource for mine road paving according to claim 1, characterized in that: The curing agent is a silicate curing agent.
5. The method for utilizing lead-zinc ore slag as a resource for mine road paving according to claim 1, characterized in that: The expansion agent is silicon oxide, polycarboxylic acid type collapse-preventing agent, shrinkage-reducing polycarboxylic acid water-reducing agent, styrene copolymer carboxyl compound, and lignin sulfonate mixture.
Citation Information
Patent Citations
Road surface structure and construction method thereof
CN108316079A
Cementing agent composition for filling mine, and preparation method thereof
CN112194451A